Health intentions and behaviors of health app owners: a cross-sectional study. Issue 7 (9th August 2019) - Tuman, Malwina; Moyer, Anne
ABSTRACT: Mobile devices have become widely popular in recent years. This popularity has been accompanied by the adoption of technologies created for those devices such as mobile applications (apps), many of which have been designed to facilitate achieving health goals. This study examined health-related intentions and behaviors, and their associations with mobile health app ownership in a large, nationally representative sample. Data from the Health Information National Trends Survey (HINTS) from the 2014 collection wave were analyzed. Expressing greater intentions to lose weight and to exercise was associated with owning mobile health apps. However, health app owners did not significantly differ from non-owners in their reported health behaviors in the domains of eating, exercise, and sedentary time. Although we do not know that the health apps that the app owners in this sample possessed were related to altering diet and exercise, this finding could suggest that health app owners do not use them, or that the ones available to them may be insufficient at eliciting and maintaining behaviors supporting relevant health intentions, suggesting an opportunity to leverage the capacities of mHealth technologies to produce more effective interventions delivered by apps informed by health behavior change theories.